Revitalisasi Kemampuan Adaptasi Birokrasi Garis Depan Pada Kebiasaan Baru Penyelenggaraan Pelayanan Publik Di Kota Makassar - Parawu, Hafiz Elfiansya; Mahsyar, Abdul; Sudarmi, Sudarmi (Professional: Jurnal Komunikasi dan Administrasi Publik, 2024)
Street level bureaucracy is one of the main elements in providing public services in dealing with the impact of the Covid-19 pandemic. This research specifically aims to identify the revitalization of the role of Ballaparang Sub District and Gunung Sari Sub District officials, Rappocini District, Makassar Municipality in providing government administration services and other services to the community during the implementation period of the new normal policy. The type of research used is qualitative with a descriptive approach. The results of the research show that the Ballaparang and Gunung Sari Sub District officials have demonstrated good abilities in responding to and overcoming problems in the delivery of public services in the new normal era and challenges from the aspects of efficiency, effectiveness and fairness in the delivery of public services can be overcome.